2017
DOI: 10.7554/elife.25624
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of β-lactam/β-lactamase inhibitor combination is linked to WhiB4-mediated changes in redox physiology of Mycobacterium tuberculosis

Abstract: Mycobacterium tuberculosis (Mtb) expresses a broad-spectrum β-lactamase (BlaC) that mediates resistance to one of the highly effective antibacterials, β-lactams. Nonetheless, β-lactams showed mycobactericidal activity in combination with β-lactamase inhibitor, clavulanate (Clav). However, the mechanistic aspects of how Mtb responds to β-lactams such as Amoxicillin in combination with Clav (referred as Augmentin [AG]) are not clear. Here, we identified cytoplasmic redox potential and intracellular redox sensor,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 83 publications
0
49
0
Order By: Relevance
“…Mouse infection and isolation of exosomes from serum and lungs. BALB/c mice (6 to 8 weeks old) were infected with M. tuberculosis 100 bacilli per lung by aerosol or left uninfected as described previously (100). At 20 weeks p.i., animals were euthanized and serum and lungs were collected.…”
Section: Methodsmentioning
confidence: 99%
“…Mouse infection and isolation of exosomes from serum and lungs. BALB/c mice (6 to 8 weeks old) were infected with M. tuberculosis 100 bacilli per lung by aerosol or left uninfected as described previously (100). At 20 weeks p.i., animals were euthanized and serum and lungs were collected.…”
Section: Methodsmentioning
confidence: 99%
“…The notorious tendency of M. tuberculosis with the conjunction of prolonged treatment regimens shows drug resistant which is developed in different stages (Connolly et al 2007). Also the expression of β-lactamase is considered as the most significant causes for developing intrinsic resistant to these antibiotics (Mishra et al 2017). In line with this context, recent studies reported that the sensitivity to M. tuberculosis is increased by 8-256 fold upon the deletion of chromosomal class A (Ambler)…”
Section: Introductionmentioning
confidence: 98%
“…Using Mrx1-roGFP2, E MSH changes were studied in drug-resistant Mtb isolates, during intracellular replication and persistence in the acidic phagosomes of macrophages [36] , [37] , [38] . Mrx1-roGFP2 was also applied as tool in drug research to screen for ROS-generating anti-tuberculosis drugs or to reveal the mode of action of combination therapies based on E MSH changes [36] , [39] , [40] , [41] . The Mtb population exhibited redox heterogeneity of E MSH during infection inside macrophages which was dependent on sub-vacuolar compartments and the cytoplasmic acidification controlled by WhiB3 [36] , [38] .…”
Section: Introductionmentioning
confidence: 99%